2013
DOI: 10.1177/1533317513517034
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Grief and Health-Related Quality of Life for Caregivers of People With Dementia

Abstract: The aim of this qualitative study was to explore key positive and negative factors that impact on grief resolution and health outcomes of caregivers who were caring, or had cared, for a family member with dementia who had died. The study was a scoping study and involved face-to-face interviews with these family caregivers (N = 13). Results indicated a complex interaction of issues (many unique to dementia caregiving) which in different combinations acted as protective or risk factors for caregiver outcomes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Participants' sense of loss and anticipatory grief, which had a major impact on their psychological well-being and overall subjective QoL, are also shown in the literature as impacting on carers' ability to cope with the stressors, leading to depressive symptoms and lower levels of subjective QoL (Garand et al, 2012;Shuter, Beattie, & Edwards, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Participants' sense of loss and anticipatory grief, which had a major impact on their psychological well-being and overall subjective QoL, are also shown in the literature as impacting on carers' ability to cope with the stressors, leading to depressive symptoms and lower levels of subjective QoL (Garand et al, 2012;Shuter, Beattie, & Edwards, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…5,24 A study found that caregivers that provided care for a longer duration of time had higher levels of resilience.…”
Section: Resilience and Psychological Factors (N = 15)mentioning
confidence: 99%
“…Shuter et al 24 Explored key positive and negative factors that have an impact on grief resolution and health outcomes of caregivers. n = 13 Does not specify type of dementia.…”
Section: N = 18mentioning
confidence: 99%
“…For example, Shuter et al (2014) situated a grounded theory study in two models based on adaptation overtime, Kramer's Conceptual Model of Caregiver Adaption (1997) and the Cognitive-based Behavioural Conceptualisation of Complicated Grief (Boelen, van den Hout, & van den Bout, 2006). Within this framework, resilience was identified as an intrinsic factor that bolstered the caregivers' adaptation to the decline of dementia.…”
Section: 1mentioning
confidence: 99%
“…Thus, resilience in caregivers is successful adaptation to a care situation while maintaining health and fulfilling the caregiving role (Giesbrecht et al, 2015;Lin et al, 2013;Nabors et al, 2013;Ruiz-Robledillo et al, 2014). This successful adaptation is not only influenced by individual factors and intrinsic resources (Shuter et al, 2014), but also by family and socioenvironmental factors (Giesbrecht et al, 2015;Lin et al, 2013;Luthar et al, 2000). Studies focused only on individual factors inadequately describe the concept of resilience because "environmental conditions help shape resilience by mitigating the negative effects of adversity" (Amzel et al, 2013).…”
Section: 2mentioning
confidence: 99%